Ukraine's international legion and its volunteers - Maja Touzari Janesdatter Greenwood (Danish Institute for International Studies (DIIS), 2024)
The Russian war on Ukraine brought many surprises, one of which was the establishment of the International Legion for Defence of Ukraine. Thousands of international volunteers from numerous countries including Denmark flocked to join the legion - some veterans from their national armies, some untrained novices, and some with violent histories from extremist environments or other conflict zones. They were met by a chaotic scene in which an entire legion was being improvised in real-time, where security was low, and where informal militias were operating alongside the official legion. This report outlines the improvisation of the legion and tells the story of Danish volunteers. It highlights how this mobilisation prompts a reevaluation of conventional notions of warfare and the role of individuals within it, potentially challenging governments to determine their stance towards citizens participating in foreign conflicts. Finally, it offers recommendations for the development of rehabilitation initiatives for returned volunteers.
Keywords: 300; Ukraine; International Legion for Defence of Ukraine; Russia; Denmark; USA; Foreign fighters; Zelenskyy